The Role of Local Government in Protecting the Rights of Older People: The Case of Intergenerational Self-help Clubs in Vietnam: Role of local governments in protecting rights of older people - Giang, Long Thanh; Chu, Viet-Nga; Tran, Bich-Thuy (Local Administration Journal, 2020)
This article, using data and information from different sources such as those from Help Age Vietnam (HAV), Vietnam Association of the Elderly (VAE) and Vietnam Women’s Union (VWU), provides an overview on the function and activities of the Intergenerational Self-Help Clubs (ISHC) for older people in Vietnam, through which the role of local government is discussed in order to show how they have contributed to protecting rights for older people in various aspects such as income security, health care, and social care. As community-based organizations with three main characteristics (multiple activities, community ownership, and strong connection with local government), ISHC showed their importance in protecting rights for older people at the local level, in which active involvement and actions of local government have facilitated these functions significantly. Given the increasing number of older people due to the rapidly-aging population, expansion of ISHC would facilitate more protection of rights for older people and, as such, the role of local government should be more important than ever.